KAJIAN ETNOBOTANI POHON KAPUR BARUS DI KECAMATAN BARUS KABUPATEN TAPANULI TENGAH - Tanjung, Rizkan Azhari; Mahyuny, Siska Rita; Ariska, Raja Novi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Barus District has long been known as an important trading port on the west coast of Sumatra and historically served as a gateway for the spice trade, including kapur barus (camphor). The ethnobotanical significance of kapur barus (Dryobalanops aromatica), a tree species native to Indonesia, has been recognized since ancient times by Arab and Chinese traders. However, the declining interest of younger generations in traditional plant-based knowledge threatens the preservation of this cultural heritage. Preliminary observations indicate that information regarding the ethnobotany of kapur barus in Barus District remains limited, and no specific study has been conducted in the area. This research aims to document ethnobotanical knowledge related to kapur barus among local communities in Barus District, Central Tapanuli Regency. The study employed a qualitative descriptive approach with field-based methods. Informants were selected purposively, consisting of eight community representatives. Data were collected through semi-structured interviews guided by a question list. The results reveal that kapur barus is utilized in various aspects of local life, including botany, ethnopharmacology, ethnoeconomics, ethnolinguistics, and ethnoecology. The species plays an important economic, medicinal, and cultural role for the people of Barus District. This study underscores the significance of preserving traditional ethnobotanical knowledge and highlights the potential for its sustainable development.